Coordination between primary and secondary healthcare in Denmark and Sweden - Sarah Wadmann; Martin Strandberg-Larsen; Karsten Vrangbæk (International Journal of Integrated Care, 2009)
Introduction: Insights into effective policy strategies for improved coordination of care is needed. In this study we describe and compare the policy strategies chosen in Denmark and Sweden, and discuss them in relation to interorganisational network theory. Policy practice: The policy initiatives to improve collaboration between primary and secondary healthcare in Denmark and Sweden include legislation and agreements aiming at clarifying areas of responsibility and defining requirements, creation of links across organisational boarders. In Denmark many initiatives have been centrally induced, while development of local solutions is more prominent in Sweden. Many Danish initiatives target the administrative level, while in Sweden initiatives are also directed at the operational level. In both countries economic incentives for collaboration are weak or lacking, and use of sanctions as a regulatory mean is limited. Discussion and conclusion: Despite a variety of policy initiatives, lacking or poorly developed structures to support implementation function as barriers for coordination. The two cases illustrate that even in two relatively coherent health systems, with regional management of both the hospital and general practice sector, there are issues to resolve in regard to administrative and operational coordination. The interorganisational network literature can provide useful tools and concepts for interpreting such issues.